2017
DOI: 10.1007/s00590-017-1904-1
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar and sacral pedicle screw placement using a template does not improve the midterm pain and disability outcome in comparison with free-hand method

Abstract: The application of a drill guide template for pedicle screw placement is not more effective in reducing pain and disability after midterm follow-up in comparison with the free-hand technique. However, it reduces the cortex perforation incidence. Concerning this evidence, a drill guide is still an additional tool that could in the future potentially compete with other screw placement techniques.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 25 publications
0
11
0
1
Order By: Relevance
“…Then, 4 animal studies and 4 cadaver specimen studies were excluded from the 21 studies that met the inclusion criteria. Finally, 13 eligible trials [14,[17][18][19][20][21][22][23][24][25][26][27][28] were included in this meta-analysis. The flow diagram for the literature selection is shown in Fig.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Then, 4 animal studies and 4 cadaver specimen studies were excluded from the 21 studies that met the inclusion criteria. Finally, 13 eligible trials [14,[17][18][19][20][21][22][23][24][25][26][27][28] were included in this meta-analysis. The flow diagram for the literature selection is shown in Fig.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…Six of the seven randomized controlled trials [14,17,18,[22][23][24] had a low risk of performance bias due to the random sequence generation method, and only one study [27] had a high risk due to selection bias. Five studies [18,[22][23][24]27] had a high risk of performance bias with due to the method of blinding the participants and personnel, and the other studies had an unclear risk [14,17]. One study [24] had a high risk of detection bias, and another study [22] had a high risk of attrition bias.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Éltes et al (2016) [32] created a template for sacrum with two screw-guiding structures using photoactive 3D printing technology. Merc et al (2017) [33] concluded that although the template for sacral pedicle screw placement does not reduce pain and disability than the free-hand technique, however, does reduce the incidence of cortex perforation.…”
Section: Introductionmentioning
confidence: 99%